Emergence and characterisation of vanB vancomycin-resistant Enterococcus faecalis in Rio de Janeiro, Brazil - Vânia Lúcia Carreira Merquior; Adriana Rocha Faria; Filomena Soares Pereira da Rocha; Jaqueline Martins Morais; Felipe Piedade Gonçalves Neves; Lúcia Martins Teixeira (Memorias do Instituto Oswaldo Cruz, 2012)
Here we describe the detection and characterisation of three isolates of vancomycin-resistant VanB-type Enterococcus faecalis. Sequence analysis suggested that these isolates harboured the vanB1 gene. The isolates were susceptible to the majority of antimicrobial agents tested, with the exception of chloramphenicol, erythromycin and vancomycin, and showed distinct profiles of high-level resistance to aminoglycosides. Analysis of the clonal relatedness of the vanB E. faecalis isolates showed similar pulsed-field gel electrophoresis profiles. To our knowledge, this is the first report of the occurrence of enterococcal strains carrying vanB genes in Brazil.